Effect of Drip Fertigation of Nitrogen, Potassium and Microbial Consortium on Growth, Yield, Water Productivity and Economics of Rabi Maize (Zea mays L.) - Kiran, A. Sai; Kumar, K. Avil; Devi, M. Uma; Naik, B. Balaji; Triveni, S. (International Journal of Bio-resource and Stress Management, 2022)
A field experiment was conducted on maize (Zea mays L.) during rabi (November to February), 2018–19 to study the effect of drip fertigation of Nitrogen (N), Potassium (K) and microbial consortium (MC) on growth, yield, water productivity and economics at Water Technology Centre, PJTSAU, Hyderabad, Telangana state, India. The experiment was laid out in randomised block design and replicated thrice. The treatments, comprising of two fertility levels viz., 75% and 100% recommended dose (RD) of N and K as first factor and biofertigation of Microbial Consortium (MC) as second factor. The interaction effect between RD of N and K and biofertigation of MC was not significant. Significantly higher LAI, DMP, grain yield and water productivity was recorded with fertigation of 100% RD N and K compared to 75% RD N and K. Biofertigation of MC 5 times and 3 times recorded significantly higher LAI, DMP, grain yield and water productivity. Net returns recorded with fertigation of 75% and 100% RD of N and K were not significantly different. Among biofertigation of MC, significantly higher net returns were observed in biofertigation of MC five times and was on par with biofertigation of MC three times. 75% RD of N and K recorded higher B:C ratio and was on par with 100% RD N and K in fertigation levels. Among biofertigation of MC, there was no significant difference in B:C ratio was observed between biofertigation of MC five times and three times and were significantly superior over soil application of MC.